A Multifunctional Tyrosine‐Immobilized PAH Molecule as a Universal Cathode Interlayer Enables High‐Efficiency Inverted Polymer Solar Cells. Issue 21 (3rd August 2021) - Kim, Young‐O; Moon, Byung Joon; Lee, Aram; Kim, Jin Il; Lee, Seoung‐Ki; Lee, Yoon‐Sik; Bae, Sukang; Hong, Byung Hee; Jung, Yong Chae
Abstract: Among the various biological components in the photosynthesis reaction, tyrosine (Tyr) is considered crucial for facilitation of charge/proton transfer. However, the practical realization of this capability in recent artificial solar‐energy conversion systems is limited by the required alignment of Tyr molecules with both host materials and themselves. In this work, Tyr−perylene diimide−Tyr (PDI‐Y) is designed for implementation of a molecular‐based artificial photosystem II, where PDI and Tyr act as an antenna and internal mediator, respectively. The experimental and theoretical investigations prove that the presence of covalently immobilized Tyr can enhance the intramolecular charge separation, leading to a significant reduction of the exciton recombination probability. To explore the feasibility of using Tyr‐immobilized PDI in practical applications, PDI‐Y is applied as a universal cathode interlayer in an inverted polymer solar cell (iPSC). The result demonstrates potential multifunctional roles of PDI‐Y as a sub‐photosensitizer and electron transport layer, leading to a superior photovoltaic performance in both fullerene (PC71 BM) and nonfullerene (Y6) based iPSCs. Consequently, the simple yet efficient Tyr‐immobilization approach is expected to offer tremendous opportunities for the advancement of electronic and optoelectronic applications. Abstract : Tyrosine‐immobilized perylene (PDI‐Y) is designed as a molecular‐based artificial photosystem II, where the presence of covalently immobilized tyrosine can enhance the intramolecular charge separation, thereby reducing the exciton recombination probability. Also, it is found that the introduction of PDI‐Y as an interlayer can enhance the photovoltaic performance of inverted polymer solar cells due to its light‐harvesting ability and charge generation/transport capability.